PENERAPAN PENDEKATAN QUANTUM TEACHING-LEARNING DALAM PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH NEGERI MEMPAWAH - Adi Nurdiansyah; Asrori Asrori; Kaswari Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to describe the application of thematic learning using the quantum teaching approach and quantum learning in the classroom. This study uses direct observation techniques, qualitative approaches and triangulation techniques. As for formulation of the problem described in this study include how the teacher plans for thematic learning, teacher implementation of thematic learning, and teacher evaluation of thematic learning inclass IV. In planning thematic teachers prepare documents in the form of RPP, assessment rubric and assessment portfolio. Next the teacher conducts thematic learning activities inside and outside the classroom. Then the teacher evaluates the learning outcomes at the end of the learning activity. From the thematic learning process activities using the quantum teaching learning approach, the results obtained from planning, implementation and evaluation are teachers who have planned learning by preparing documents in the form of syllabus and lesson plans, then the teacher carries out learning activities based on the plans that have been prepared. After carrying out learning activities the teacher evaluates the achievement of students in learning activities. Based on the description above it can be concluded that the application of thematic learning with the quantum teaching learning approach has been implemented. Keywords: Quantum Learning, Quantum Teaching, Thematic Learning